WormPose: Image synthesis and convolutional networks for pose estimation in C. elegans - Hebert, Laetitia; Ahamed, Tosif; Costa, Antonio C.; O’Shaughnessy, Liam; Stephens, Greg J. (PLoS computational biology, 2021)
An important model system for understanding genes, neurons and behavior, the nematode worm C . elegans naturally moves through a variety of complex postures, for which estimation from video data is challenging. We introduce an open-source Python package, WormPose, for 2D pose estimation in C . elegans , including self-occluded, coiled shapes. We leverage advances in machine vision afforded from convolutional neural networks and introduce a synthetic yet realistic generative model for images of worm posture, thus avoiding the need for human-labeled training. WormPose is effective and adaptable for imaging conditions across worm tracking efforts. We quantify pose estimation using synthetic data as well as N2 and mutant worms in on-food conditions. We further demonstrate WormPose by analyzing long (∼ 8 hour), fast-sampled (∼ 30 Hz) recordings of on-food N2 worms to provide a posture-scale analysis of roaming/dwelling behaviors.